FIGO staging of endometrial cancer: 2023 - Berek, Jonathan S.; Matias‐Guiu, Xavier; Creutzberg, Carien; Fotopoulou, Christina; Gaffney, David; Kehoe, Sean; Lindemann, Kristina; Mutch, David; Concin, Nicole; Berek, Jonathan S.; Wilailak, Sarikapan; Kehoe, Sean; et al. (International journal of gynecology and obstetrics, 2023)
Introduction Many advances in the understanding of the pathologic and molecular features of endometrial cancer have occurred since the FIGO staging was last updated in 2009. Substantially more outcome and biological behavior data are now available regarding the several histological types. Molecular and genetic findings have accelerated since the publication of The Cancer Genome Atlas (TCGA) data and provide improved clarity on the diverse biological nature of this collection of endometrial cancers and their differing prognostic outcomes. The goals of the new staging system are to better define these prognostic groups and create substages that indicate more appropriate surgical, radiation, and systemic therapies. Methods The FIGO Women's Cancer Committee appointed a Subcommittee on Endometrial Cancer Staging in October 2021, represented by the authors. Since then, the committee members have met frequently and reviewed new and established evidence on the treatment, prognosis, and survival of endometrial cancer. Based on these data, opportunities for improvements in the categorization and stratification of these factors were identified in each of the four stages. Data and analyses from the molecular and histological classifications performed and published in the recently developed ESGO/ESTRO/ESP guidelines were used as a template for adding the new subclassifications to the proposed molecular and histological staging system. Results Based on the existing evidence, the substages were defined as follows: Stage I (IA1): non‐aggressive histological type of endometrial carcinoma limited to a polyp or confined to the endometrium; (IA2) non‐aggressive histological types of endometrium involving less than 50% of the myometrium with no or focal lymphovascular space invasion (LVSI) as defined by WHO criteria; (IA3) low‐grade endometrioid carcinomas limited to the uterus with simultaneous low‐grade endometrioid ovarian involvement; (IB) non‐aggressive histological types involving 50% or more of the myometrium with no LVSI or focal LVSI; (IC) aggressive histological types, i.e. serous, high‐grade endometrioid, clear cell, carcinosarcomas, undifferentiated, mixed, and other unusual types without any myometrial invasion. Stage II (IIA): non‐aggressive histological types that infiltrate the cervical stroma; (IIB) non‐aggressive histological types that have substantial LVSI; or (IIC) aggressive histological types with any myometrial invasion. Stage III (IIIA): differentiating between adnexal versus uterine serosa infiltration; (IIIB) infiltration of vagina/parametria and pelvic peritoneal metastasis; and (IIIC) refinements for lymph node metastasis to pelvic and para‐aortic lymph nodes, including micrometastasis and macrometastasis. Stage IV (IVA): locally advanced disease infiltrating the bladder or rectal mucosa; (IVB) extrapelvic peritoneal metastasis; and (IVC) distant metastasis. The performance of complete molecular classification (POLEmut, MMRd, NSMP, p53abn) is encouraged in all endometrial cancers. If the molecular subtype is known, this is recorded in the FIGO stage by the addition of “m” for molecular classification, and a subscript indicating the specific molecular subtype. When molecular classification reveals p53abn or POLEmut status in Stages I and II, this results in upstaging or downstaging of the disease (IICmp53abn or IAmPOLEmut). Summary The updated 2023 staging of endometrial cancer includes the various histological types, tumor patterns, and molecular classification to better reflect the improved understanding of the complex nature of the several types of endometrial carcinoma and their underlying biologic behavior. The changes incorporated in the 2023 staging system should provide a more evidence‐based context for treatment recommendations and for the more refined future collection of outcome and survival data.